PKM on The Development of Indonesian Community (Permai) Pulau Pinang in the Implementation of the Accounting Cycle and Financial Reporting - SETIYAWATI, Hari; PRATIWI, Riri; RAHMAD, Khozaeni Bin; ZULKAFI, Abdul Hadi; FEBRIANA, Vivi; METACESARI, Magfirah (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
This Community Service activity was conducted in collaboration with the Indonesian Community Association (PERMAI), a non-political NGO based in George Town, Penang, Malaysia. PERMAI supports Indonesians living in Malaysia, including businesspeople, workers, teachers, and students, and is active in social, educational, and cultural fields. A major challenge for PERMAI members, especially business owners, is the lack of accounting knowledge, which leads to poor financial record-keeping and reporting, hindering business growth. To tackle this issue, the PKM team provided basic accounting training covering accounting concepts, the accounting cycle, and practical skills from recording transactions to preparing financial reports. The training used interactive lectures, discussions, and hands-on practice with relevant case studies. The activity successfully improved participants’ understanding of accounting’s role in managing businesses. Participants gained the ability to independently record financial transactions and prepare simple financial reports. These results demonstrate that basic accounting training enhances business owners’ capacity to manage their operations more professionally and sustainably.